2015
DOI: 10.1111/cei.12636
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A in serum: an old acquaintance as a new prognostic biomarker in idiopathic pulmonary fibrosis

Abstract: SummaryImmunoglobulin (Ig)A is an important immunoglobulin in mucosal immunity and protects the lungs against invading pathogens. The production of IgA is regulated by transforming growth factor (TGF)-b, a versatile cytokine and key player in the pathogenesis of pulmonary fibrosis. TGF-b is up-regulated in patients with idiopathic pulmonary fibrosis (IPF), but difficult to use as a biomarker. The aim of this study was to evaluate the prognostic value of IgA in serum in patients with IPF. We examined IgA levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 29 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…). However, it must be noted that a serum IgA level in which the majority exists in the form of mIgA was reported to be a prognostic marker for IPF . Although we did not detect any pathogenic role or mIgA on activation of NHLFs, the level of mIgA may be linked to the level of sIgA because both mIgA and dIgA, a component of sIgA, are produced by plasma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). However, it must be noted that a serum IgA level in which the majority exists in the form of mIgA was reported to be a prognostic marker for IPF . Although we did not detect any pathogenic role or mIgA on activation of NHLFs, the level of mIgA may be linked to the level of sIgA because both mIgA and dIgA, a component of sIgA, are produced by plasma cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that the level of serum IgA can be used as a prognostic marker for idiopathic pulmonary fibrosis (IPF): a high level of serum IgA was associated with poor survival of IPF patients . Because transforming growth factor (TGF)‐β, the most potent cytokine involved in fibrogenesis in IPF, is critical for mucosal IgA responses , it is conceivable that IgA might play an important role in the pathogenesis of IPF.…”
Section: Introductionmentioning
confidence: 99%
“…The serum IgA concentration is reported to reflect the severity of liver fibrosis in non‐alcoholic fatty liver disease and also the prognosis of IPF . While IgA can be a biomarker of fibrosis based on these findings, it is not clear whether IgA itself up‐regulates profibrotic cytokine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we see that idiopathic pulmonary fibrosis (IPF), is grouped together with common variable immunodeficiency and immunoglobulin alpha (IgA) deficiency. Indeed, IgA in serum has recently been proposed as a prognostic biomarker for IPF 33 . While space limitations preclude us from discussing every disease class in detail, given the high cohesiveness of multiplex disease classes, readers can draw similar possibly interesting disease-disease interactions from any of the classes using Supplementary Table 1 as reference.…”
Section: Resultsmentioning
confidence: 99%